Pengembangan E-LKPD Berbasis Model Inkuiri Terbimbing Pada Pembelajaran IPAS Di Kelas IV Sekolah Dasar - Deri Musfita; Fetri Yeni J; Jasrial; Zuwirna (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop an Electronic Student Worksheet (E-LKPD) based on the guided inquiry model for IPAS learning in Grade IV elementary school students. The E-LKPD was developed using the 4-D model, which consists of the Define, Design, Develop, and Disseminate stages. The results show that the E-LKPD has very high validity, with material validity scoring 95%, media validity 83%, and language validity 100%. The practicality test conducted at SDN 01 Batang Palupuh showed that the product is highly practical, with teacher ratings reaching 91% and student ratings at 91.1%. The effectiveness of the E-LKPD was tested using pre-test and post-test designs, which showed a significant improvement in student understanding, with an N-Gain score of 0.58. Based on the trial results, it can be concluded that the E-LKPD based on the guided inquiry model is effective in enhancing student engagement and understanding of IPAS concepts in Grade IV elementary school students.